Drug release properties of nanostructured lipid, liposome, oil-in-water microemulsion and κ-carrageenan-chitosan nanoparticle / Yew Han Choi - Yew, Han Choi (2017)
he dissolution and permeation of active ingredient from its carrier system are the key factors in affecting its efficacy. An ability to control active ingredient’s rate of release not only enable optimum therapeutic effect but also lower the possibility of adverse effect. This study aimed to investigate the physicochemical properties, encapsulation efficiency and release profile of four types of nanocarrier with different disperse and continuous phases. The four nanocarriers include (i) nanostructured lipid whereby the lipid matrix is dispersed in aqueous phase; (ii) liposome consists of outer lipid bilayer and aqueous core which also dispersed in aqueous phase; (iii) water-in-oil microemulsion has water droplet as disperse phase and olive oil as continuous phase; last but not least, (iv) κ-carrageenan-chitosan nanoparticle which has hydrophilic polymer dispersed in aqueous phase. Three low molecular weight active ingredients with different solubility in water which are ascorbic acid, caffeine and lidocaine were then encapsulated in those nanocarriers. Based on the physicochemical evaluations, the formulated nanocarriers were stable for at least 30 days with polydispersity of < 0.4 when kept at 30 ˚C. The particle sizes of nanocarriers were in the ascending order of 30 nm, 100 nm, 250 nm, and 400 nm for microemulsion, liposome, nanostructured lipid, and κ-carrageenan-chitosan nanoparticle respectively. Encapsulation efficiency revealed that liposome and nanostructrured lipid which have lipid surface, were excellent for lidocaine encapsulation up to 80% while water-in-oil microemulsion and κ-carrageenan-chitosan nanoparticle have better preference towards more water soluble ascorbic acid with 70% encapsulation efficiency. All nanocarriers exhibit controlled release property whereby the active ingredients’ rates of release from those nanocarriers were slower than free active ingredients. The average time required for in vitro 50% active ingredients to be released from nanocarriers were in the order of liposome (7 hours), nanostructured lipid (9 hours), water-in-oil microemulsion (33 hours), and lastly, κ-carrageenan-chitosan nanoparticle (more than 48 hours) irrespective to the types of active ingredients. The reason for a shorter time to achieve 50% release in liposome and nanostructured lipid is due to initial burst release from the surface of the nanocarrier which is then followed by sustained release from the matrix core. Nanostructured lipid which requires longer release time than liposome was accountable to the fact that longer diffusion path length for the homogenized nanocarrier to diffuse due to its larger size. The extended period of release time for water-in-oil microemulsion is plausibly due to interfacial barrier and different permeability coefficient of donor and receptor chamber in Franz diffusion cell. κ-carrageenan-chitosan nanoparticle which extensively prolonged the release time could be attributed by electrostatic interaction between the active ingredients and the polymer. The in vitro release profile of those nanocarriers showing that they could be tailored for different applications, hence aided in solving solubility and permeability problems, enhancing therapeutic effects and lastly, minimizing or eliminating possible side effects.